Moda, reificación y utopía: zapatillas de lujo y la estética worn out - Patiño Núñez, Alberto (2023)
This article analyses some examples of what is usually known as "designer" sneakers ins cribed in the so called worn out aesthetic trend. lt describes practices and discourses of the fashion industry, and the luxury and sumptuousness with which it is usually associa ted. lt identifies the cultural framework and the fashion market as references of identities and ideals of the present time. Based on the critical and cultural theory of authors such as Fredric Jameson and Slavoj ZiZek, it reviews some ideas centered on conceptions of the past, the construction of identity and the creation of social ties. From this perspective, it is questioned whether the meaning of the aesthetic is depoliticized or if it is rather what is called an ideological production.